The association of dietary approaches to stop hypertension (DASH) with the odds of diabetic nephropathy and metabolic markers in women: a case-control study - Atieh Mirzababaei; Faezeh Abaj; Sara Hajishizari; Niki Bahrampour; Sahar Noori; Ahmad Mujtaba Barekzai; Dorsa Hosseininasab; Cain C. T. Clark; Khadijeh Mirzaei (BMC, 2023)
Abstract Objectives Epidemiologic studies have reported that diet is associated with diabetes and its complications through different pathways. We sought to examine the associations between the Dietary Approaches to Stop Hypertension (DASH) diet and the odds of diabetic nephropathy (DN) developing in Iranian women with existing type 2 diabetes. Methods In this case-control study, 105 women with DN and 105 controls, matched for age and diabetes duration, were selected from the Kowsar Diabetes Clinic in Semnan, Iran. DASH, estimated using dietary intake, was assessed using a validated and reliable food frequency questionnaire with 147 items. Anthropometric measurements were assessed for all subjects. Logistic regression was performed to examine the association between DASH and the odds of developing DN. Results After controlling for potential confounders, subjects in the highest intake of DASH diet adherence have 84% lower odds of DN, compared to those with the lowest intake (OR = 0.16, 95% CI = 0.07-0.34, P < 0.001). Among DASH diet subcategories, intakes of vegetables (80%), fruits (88%), nuts and legumes (87%), and low-fat dairy (73%) decreased the risk of DN after adjustment for confounders (P < 0.001). Conclusions This study showed that the DASH diet is associated with lower odds of DN development in women with type 2 diabetes.